Mathematics (T) - Chen, Chong Yew; Chin, Siew Wui; Khoo, Ea Sin; Khor, Seng Chye (PRE-U STPM Text, 2022)
PRE-U STPM Text Mathematics (T) Semester 3 specially designed for students who are sitting for the STPM examination. The comprehensive notes and practices are based on the latest syllabus and exam format set by Majlis Peperiksaan Malaysia. This book will provide you with the necessary skills and strategies to excel in the subject.